2017
DOI: 10.1590/1806-90882017000200007
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus Logs Drying at High Temperatures

Abstract: The objective of this work was to evaluate the drying speed of Eucalyptus urophylla logs in high temperatures and the influence of the presence or absence of bark and also the diameter of the log in the drying rate. Eucalyptus logs 60 cm long were divided into three diameter classes: 8-12 cm; 12,1-16 cm and 16,1-20 cm. The logs were dried in a heater with forced air circulation, in the presence or absence of bark in five temperatures: 50, 75, 100, 125 and 150ºC. The mass and the initial moisture were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…presented lower density and smaller fiber dimensions. The increase in wood density is followed by an increase of fiber wall thickness and length (Oliveira et al 2010), but this was not observed in the present study. IAN 873ill.…”
Section: Chemical and Energetic Properties Basic Density And Fiber An...contrasting
confidence: 84%
“…presented lower density and smaller fiber dimensions. The increase in wood density is followed by an increase of fiber wall thickness and length (Oliveira et al 2010), but this was not observed in the present study. IAN 873ill.…”
Section: Chemical and Energetic Properties Basic Density And Fiber An...contrasting
confidence: 84%
“…Figure 5 shows that the moisture loss as a function of diameter class did not present significant differences. The effect of diameter on wood drying in eucalyptus logs was verified by Zanuncio et al (2014) and Oliveira et al (2017). These authors observed that smaller diameters had higher drying rates, compared to the ones with larger diameter logs.…”
Section: Wood Dryingmentioning
confidence: 88%
“…The drying rate is highest at the beginning with the removal of all free water until the fiber saturation moisture (Skaar 1972). After this step, the drying rate is lower due to the higher energy expenditure to remove the adsorption water until the wood reaches equilibrium moisture content, when the difference between sorption and adsorption becomes zero (Oliveira et al 2017).…”
Section: Introductionmentioning
confidence: 99%